2015
DOI: 10.17554/j.issn.2313-7177.2015.01.5
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Cellular Senescence in Lung Diseases

Abstract: cells. The detailed molecular mechanism for regulation of autophagy and cellular senescence is complex and the role of autophagy and cellular senescence is overlap significantly. We review molecular mechanisms of autophagy and cellular senescence, and summarize the role of autophagy and cellular senescence in pulmonary disease pathogeneses. AUTOPHAGYAutophagy is a process of lysosomal self-degradation that helps maintain homeostatic balance between the synthesis, degradation and recycling of cellular proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 154 publications
(211 reference statements)
0
4
0
Order By: Relevance
“…Apart from the structural cells in the airway, the innate and adaptive immune cells also play a vital role in the immunopathogenesis of CS/age-related COPD-emphysema [ 20 , 47 49 ]. The airways of COPD patients are populated with several types of immune cells such as macrophages, neutrophils, T-lymphocytes and dendritic cells, which collectively mediate the hyper-inflammatory state observed in COPD lungs [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the structural cells in the airway, the innate and adaptive immune cells also play a vital role in the immunopathogenesis of CS/age-related COPD-emphysema [ 20 , 47 49 ]. The airways of COPD patients are populated with several types of immune cells such as macrophages, neutrophils, T-lymphocytes and dendritic cells, which collectively mediate the hyper-inflammatory state observed in COPD lungs [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of autophagy in respiratory diseases is attracting increasing interest as the interface between the lungs and the environment leads to exposure to a diverse array of environmental and infectious cellular stressors. Thus, the view that the mitigation of autophagy‐mediated cellular stress plays a key regulatory role in lung pathophysiology is an attractive one . For example, a number of studies have demonstrated that autophagy may play an important role in the pathogenesis of COPD and idiopathic pulmonary fibrosis .…”
mentioning
confidence: 99%
“…[27] Impaired autophagy can cause the acceleration of fibroblast senescence, myofibroblast differentiation, and ECM production. [28] Here, this study developed a potential peptidebased treatment for IPF by restoring autophagy (Scheme 1), while earlier studies have explored the effect of antioxidants, mTOR inhibitors, and et.al on IPF treatment by regulating autophagy. [8] The impaired autophagy caused by the profibrotic factor TGF-𝛽1 has been found to evoke fibroblast to myofibroblast differen-tiation, which is a critical step in the generation of pulmonary fibrosis.…”
Section: Peptide Nanofibers Ameliorate Bleomycin-induced Pulmonary Fi...mentioning
confidence: 99%